2010
DOI: 10.1111/j.1440-1843.2010.01773.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and inflammation biomarkers may help predict the severity of community‐acquired pneumonia

Abstract: Serum levels of AT-III, D-D and CRP at admission appear to be useful biomarkers for assessing the severity of CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
3
31
1
2
Order By: Relevance
“…It could be argued that infections of airways may trigger abnormalities in inflammation and thrombosis markers, such as mean platelet volume, a link between inflammation and thrombosis. 23 Along these lines, it has been found that children with cystic fibrosis have decreased levels of mean platelet volume during the exacerbation period compared with the stable phase. 24 Similarly, mean platelet volume levels in subjects with asthma with exacerbations were lower compared with those in subjects with stable asthma.…”
Section: Discussionmentioning
confidence: 97%
“…It could be argued that infections of airways may trigger abnormalities in inflammation and thrombosis markers, such as mean platelet volume, a link between inflammation and thrombosis. 23 Along these lines, it has been found that children with cystic fibrosis have decreased levels of mean platelet volume during the exacerbation period compared with the stable phase. 24 Similarly, mean platelet volume levels in subjects with asthma with exacerbations were lower compared with those in subjects with stable asthma.…”
Section: Discussionmentioning
confidence: 97%
“…The authors found that DD elevation was a negative prognostic factor in CAP: DD 256-1000 ng/mL was combined with 2-3 fold higher mortality rate and DD > 1000 ng/mL -with 5 fold higher mortality rate [26]. Snijders et al and Agapakis et al found DD concentration significantly higher in patients with severe CAP (CURB-65 score 3-5) comparing to the others [27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, anticoagulant therapy appears to be beneficial in the treatment of lung fibrosis (10)(11)(12)(13)(14). From the standpoint of systemic inflammation, it is reported that urokinase-type plasminogen activator (u-PA) and antithrombin III (AT-III) were decreased or plasminogen activator-inhibitor 1 (PAI-1) and α2-plasmin inhibitor (PI) levels were increased in severe pneumonia (15,16). In addition, it is possible that exertional dyspnea and hypoxia due to interstitial pneumonia causes decreased mobility, resulting in deep-vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%